Comparative investigation of the ball milling role against hand grinding on microstructure, transport and pinning properties of Y3Ba5Cu8O18±δ and YBa2Cu3O7-δ. Issue 16 (November 2018) - Slimani, Y.; Hannachi, E.; Hamrita, A.; Ben Salem, M.K.; Ben Azzouz, F.; Manikandan, A.; Ben Salem, M.
Abstract: We report a comparative investigation between the two high temperature superconductor materials YBa2 Cu3 O7-δ (Y-123) and Y3 Ba5 Cu8 O18±δ (Y-358) by probing the impact of high-energy ball milling (HEBM) technique on the microstructure, transport properties and pinning capacities. Products were elaborated via the solid-state reaction (SSR) by employing two kinds of milling; hand grinding in agate mortar and HEBM in a planetary crusher. The morphology, chemical compositions and crystal structure of all produced products were explored by scanning electron microscope (SEM) along with EDXS and X-ray diffraction (XRD). The superconductivity was confirmed by electrical resistivity measurements. The transport and intra-granular critical currents densities were estimated through the current–voltage and magnetization measurements. The planetary HEBM process generates nano-sized Y-deficient Y-123 and nano-sized Y-deficient Y-358 entities dispersed in the Y-123 and Y-358 matrix, respectively. The Y-358 sample milled by HEBM exhibits the best pinning capacity. This result can be ascribed to the occurrence of more disorder in Y-358 compound compared to Y-123 one.